Analysis of Mathematics Learning Difficulty for Grade XI’s Students during Online Study on SPLDV - Imam Najib Arrazzaq; Dafid Slamet Setiana; Irham Taufiq (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to describe: (1) the difficulty of learning mathematics in class XI students of SMA N 1 Rowokele on the SPLDV material using an online learning system, (2) the factors that affect the difficulty of learning mathematics in class XI students of SMA N 1 Rowokele on the SPLDV material using the system. online learning. This type of research is descriptive qualitative. The primary data sources in this study were students of class XI SMA N 1 Rowokele. The secondary data sources are test results and interview results. Data collection techniques using observation and interviews. The research instruments are test question sheets, interview sheets, and social media (Whatsapp). In this study, researchers used the validity of the credibility test using triangulation. The data analysis technique used in this study uses the Miles and Huberman interactive analysis model which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that, (1) the subject has difficulty in understanding the SPLDV material mainly because of online learning. The subject matter is in the method of completion, namely the preparation of mathematical models and calculations. (2) The factors that influence student learning difficulties are due to the environmental conditions in which the subject is located and generally what is often experienced is the difficulty of finding a smooth internet network, thus preventing the subject from accessing information from other sources. The advice given from the school is that researchers should be able to control the class more and also prepare research instruments and the coordination of learning hours should be clearer.